2017
DOI: 10.1016/j.cjche.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer model, preparation and applications of zeolite membranes for pervaporation dehydration: A review

Abstract: Pervaporation (including vapor permeation) is a kind of new membrane separation technology, possessing the advantages of high efficiency, energy saving and convenient operation. It has promising application in the separation and purification of organic solvents. Dehydration is an important step in the production and recovery of organic solvents. Zeolite membranes have attracted wide attention for pervaporation dehydration due to their high separation performance and good thermal/chemical stability. So far, zeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 120 publications
(153 reference statements)
0
12
0
Order By: Relevance
“…The transport mechanism of permeating molecules through zeolite membranes is mainly described with the adsorption–diffusion model . The E P value is a combination of the enthalpy of sorption and the activation energy of diffusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport mechanism of permeating molecules through zeolite membranes is mainly described with the adsorption–diffusion model . The E P value is a combination of the enthalpy of sorption and the activation energy of diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…The transport mechanism of permeating molecules through zeolite membranes is mainly described with the adsorption− diffusion model. 31 The E P value is a combination of the enthalpy of sorption and the activation energy of diffusion. A positive value of E P indicates that the transport is governed by diffusion, while a negative E P suggests that the sorption is dominant in the transport process.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 91%
“…PV is a complex process that includes mass transfer and heat transfer at the same time. The models used to describe the mechanism of the transfer process include the solution-diffusion model [ 57 ], pore flow model [ 58 ], virtual phase transition solution-diffusion model [ 59 ], and irreversible thermodynamics model [ 60 ]. Among the most widely accepted is the solution-diffusion model.…”
Section: Mechanism Operation Mode and Numerical Simulation Of Thementioning
confidence: 99%
“…Probably, the resulting composite membranes can exhibit excellent performance. Several studies have shown that the development of typical composite membranes with antifouling behavior has demonstrated superior performances in diverse applications such as solvent extraction, pervaporation, desalination, volatile organic extraction from the air, microextraction, the concentration of pharmaceutical waste, and dehumidification [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%